Maintenance management system through strategic planning for public school in Malaysia - Yacob, Syamilah (2005)
The responsibilities of public property management in Malaysia including public schools are distributed among various government departments and often managed in reactive manner. Improper supervision has lead to poor performance which was due to lack of explicit property objectives. This study focused on identifying the factors of implementing maintenance management system; identifying the common practice of maintenance management; and to improve the maintenance management system through strategic planning for public school. The process includes producing a new vision statement, revising mission statement, identifying goals and objectives. In order to achieve the objectives identified, literature review was done, then the data was collected using questionnaires, the collected data was analyzed using relative index analysis. Findings had shown that although many schools have their own maintenance management system but the condition of school still at average level which means performance fall shorts of requirement expectation and need improvement due to improper maintenance practice. Hence, to improve the current maintenance management system for public school, strategic planning has been suggested in order to increase performance, to provide an effective maintenance management, provide control for maintenance activities, improve quality, cost effective satisfaction, and to optimize the maintenance processes for their school.